The twits - Dahl, Roald (Puffin Books Harmondsworth, 1987)
Mr and Mrs Twit play some horrible tricks on each other, I bet you have never met two people more revolting. They never wash, they trap birds for Bird Pie and they hate children. Find out what brilliant trick the Poly-Poly Bird and the Muggle-Wump monkeys think up for them. [Back cover]